2014
DOI: 10.1016/j.whi.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Women Know Best—Findings from a Thematic Analysis of 5,214 Surveys of Abortion Care Experience

Abstract: a b s t r a c tObjective: Patient experience is an essential component of quality care. Few studies have comprehensively evaluated patient experiences of abortion care. The objectives of this study were to describe women's experiences of abortion care in their own words, and to determine themes across patient experiences. Study Design: Data for this thematic analysis, a qualitative method that allows for the identification, analysis, and report of patterns or themes within data, come from a larger study of saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 16 publications
2
45
0
Order By: Relevance
“…We agree with McLemore et al that patient satisfaction ratings are an inadequate measure of the overall patient care experience, which they reviewed in depth in their prior publications [2,3]. Rather than repeat the information already included in the commentary sections of their papers, we opted to use the discussion section of our report to point out the differences and similarities between the findings of the studies.…”
Section: Factors Influencing Women's Satisfaction With Surgical Abortsupporting
confidence: 52%
See 1 more Smart Citation
“…We agree with McLemore et al that patient satisfaction ratings are an inadequate measure of the overall patient care experience, which they reviewed in depth in their prior publications [2,3]. Rather than repeat the information already included in the commentary sections of their papers, we opted to use the discussion section of our report to point out the differences and similarities between the findings of the studies.…”
Section: Factors Influencing Women's Satisfaction With Surgical Abortsupporting
confidence: 52%
“…We agree with McLemore et al that their qualitative assessments demonstrated that patient satisfaction is just one component of patient experience and that patient satisfaction is not the sole determinant of patient experience [2]. Taylor et al [3] evaluated whether or not patients rated their care as excellent, whereas we looked at what factors influenced their level of satisfaction, even if the patient did not consider the care as excellent.…”
Section: Factors Influencing Women's Satisfaction With Surgical Abortmentioning
confidence: 51%
“…The new California law advises following the same training protocol for experienced clinicians until 2016. Multiple publications detail the evidence generated by the study, including the safety of clinician provided aspiration abortion care, 11 multiple aspects of confidence development among clinicians while learning this skill, 12 patients' positive experience of early abortion care, 13,14 and the effective use of research to inform policy change. 15 It wasn't radical as far as the patients were concerned either.…”
Section: But How Radical Was It Really?mentioning
confidence: 99%
“…13 In surveys of patients during the study, the patients reported high satisfaction with their abortion care experience, regardless of who provided the abortion. 13,14 Rather, patients identified several factors that influenced how they ranked their care experience, including interventions to decrease shame and/or stigma, their experiences of pain and pain management, the clinical environment, and waiting times associated with their appointment. 14 These findings found no association with the type of professional (clinician or physician) who delivered the abortion care, and reflect systemic issues common in diverse health care settings.…”
Section: But How Radical Was It Really?mentioning
confidence: 99%
“…Although few studies specifically explore acceptability of surgical abortion, [8,9] we might expect overall results similar to medical abortion. Although recent research has evaluated clinic-level factors that contribute to a positive abortion experience, we have little information on which factors are most influential to a women's overall satisfaction with surgical abortion [8,10]. We performed this survey study to investigate which factors influenced women's satisfaction during first-trimester surgical abortion.…”
Section: Introductionmentioning
confidence: 99%